World Development Indicators 2010 - World Bank (World Bank, 2012)
The 1998 edition of world development indicators initiated a series of annual reports on progress toward the International development goals. In the foreword then, World Bank President James D. Wolfensohn recognized that 'by reporting regularly and systematically on progress toward the targets the international community has set for itself, the author will focus attention on the task ahead and make those responsible for advancing the development agenda accountable for results.' The same vision inspired world leaders to commit themselves to the millennium development goals. On this, the 10th anniversary of the millennium declaration, world development indicators 2010 focuses on progress toward the millennium development goals and the challenges of meeting them.